Unveiling the mechanisms for the development of rosehip-based dermatological products: an updated review - Oargă (Porumb), Diana Patricia; Cornea-Cipcigan, Mihaiela; Cordea, Mirela Irina (Frontiers in Pharmacology, 2024)
Rosa spp., commonly known as rosehips, are wild plants that have traditionally been employed as herbal remedies for the treatment of a wide range of disorders. Rosehip is a storehouse of vitamins, including A, B complex, C, and E. Among phytonutrients, vitamin C is found in the highest amount. As rosehips contain significant levels of vitamin C, they are perfect candidates for the development of skincare formulations that can be effectively used in the treatment of different skin disorders (i.e., scarring, anti-aging, hyperpigmentation, wrinkles, melasma, and atopic dermatitis). This research focuses on the vitamin C content of several Rosa sp. by their botanical and geographic origins, which according to research studies are in the following order: R. rugosa>R. montana > R. canina > R. dumalis, with lower levels in R. villosa and R. arvensis, respectively. Among rosehip species, R. canina is the most extensively studied species which also displays significant amounts of bioactive compounds, but also antioxidant, and antimicrobial activities (e.g., against Propionibacterium acnes, Staphylococcus aureus, S, epidermis, and S. haemolyticus). The investigation also highlights the use of rosehip extracts and oils to minimise the harmful effects of acne, which primarily affects teenagers in terms of their physical appearance (e.g., scarring, hyperpigmentation, imperfections), as well as their moral character (e.g., low self-confidence, bullying). Additionally, for higher vitamin C content from various rosehip species, the traditional and contemporary extraction methods are highlighted, finally choosing the best extraction method for increased bioactive compounds, with emphasis on vitamin C content. Consequently, the current research focuses on assessing the potential of rosehip extracts as medicinal agents against various skin conditions, and the use of rosehip concentrations in skincare formulations (such as toner, serum, lotion, and sunscreen). Up-to-date studies have revealed that rosehip extracts are perfect candidates as topical application products in the form of nanoemulsions. Extensive in vivo studies have revealed that rosehip extracts also exhibit specific activities against multiple skin disorders. Overall, with multiple dermatological actions and efficacies, rosehip extracts and oils are promising agents that require a thorough investigation of their functioning processes to enable their safe use in the skincare industry.